Novel VLSI Algorithm and Architecture with Good Quantization Properties for a High-Throughput Area Efficient Systolic Array Implementation of DCT. (28th December 2010) - Chiper Chiper, Doru Florin Doru Florin; Ungureanu Ungureanu, Paul Paul
Abstract : Using a specific input-restructuring sequence, a new VLSI algorithm and architecture have been derived for a high throughput memory-based systolic array VLSI implementation of a discrete cosine transform. The proposed restructuring technique transforms the DCT algorithm into a cycle-convolution and a pseudo-cycle convolution structure as basic computational forms. The proposed solution has been specially designed to have good fixed-point error performances that have been exploited to further reduce the hardware complexity and power consumption. It leads to a ROM based VLSI kernel with good quantization properties. A parallel VLSI algorithm and architecture with a good fixed point implementation appropriate for a memory-based implementation have been obtained. The proposed algorithm can be mapped onto two linear systolic arrays with similar length and form. They can be further efficiently merged into a single array using an appropriate hardware sharing technique. A highly efficient VLSI chip can be thus obtained with appealing features as good architectural topology, processing speed, hardware complexity and I/O costs. Moreover, the proposed solution substantially reduces the hardware overhead involved by the pre-processing stage that for short length DCT consumes an important percentage of the chip area.